2020
DOI: 10.1158/1078-0432.ccr-19-1418
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Super-Enhancer–Associated Oncogenes in Osteosarcoma with THZ2, a Covalent CDK7 Inhibitor

Abstract: Despite the development of new diagnostic and advanced treatment strategies, the prognosis of patients with osteosarcoma remains poor. It is thus urgent to identify novel and effective targets and treatment regimens for osteosarcoma patients. In this study, we found that super-enhancer-associated genes contribute to the malignant potential of osteosarcoma. Knockdown of CDK7 reduced the phosphorylation of the RNA polymerase II (RNAPII) C-terminal repeat domain (CTD), which is enriched in super-enhancers and sup… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 53 publications
0
43
0
Order By: Relevance
“…We found that super enhancer plays an important role in the occurrence and development of osteosarcoma [40] . Further screening and sequencing results showed that gls1 gene associated with super enhancer may play an important role.…”
Section: Introductionmentioning
confidence: 79%
“…We found that super enhancer plays an important role in the occurrence and development of osteosarcoma [40] . Further screening and sequencing results showed that gls1 gene associated with super enhancer may play an important role.…”
Section: Introductionmentioning
confidence: 79%
“…Chen et al (2018) have experimentally demonstrated that SE-inhibitors are promising small-molecule drugs for patients with osteosarcoma by targeting the MYC signaling pathway in osteosarcoma. Zhang et al (2020) found THZ2 can target SE-associated oncogenes in osteosarcoma. Using ChIP-Seq, they found that SEs are associated with oncogenic genes in osteosarcoma cells.…”
Section: Ses In Osteosarcomamentioning
confidence: 98%
“… Zhang et al (2020) found THZ2 can target SE-associated oncogenes in osteosarcoma. Using ChIP-Seq, they found that SEs are associated with oncogenic genes in osteosarcoma cells.…”
Section: Ses In Bone-related Diseasesmentioning
confidence: 98%
See 2 more Smart Citations